THE RELATIONSHIP BETWEEN THE MARKETING MIX OF MOBILE DENTAL SERVICES AND THE INTEREST IN REPEAT VISITS BY PATIENTS AT THE DENTAL HOSPITAL OF JENDERAL SOEDIRMAN UNIVERSITY - Mudrikah, Tania Salsa Belani; Prakosa, Aditya Priagung; Kumala, Lukita Intan; Cahyani, Inneke; Widyaningsih, Pratiwi Nur (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2025)
Introduction: Educational Dental Hospital of Jenderal Soedirman Purwokerto has been facing problems regarding patient visit numbers in recent years. Evaluation of the marketing using mobile dental services is necessary to determine how effective the service is. One of the strategic efforts made is to use the marketing mix concept, which consists of 7 components: product, price, place, promotion, people, process, and physical evidence. Aim: This study aims to understand the correlation between the marketing mix of mobile dental services and patient revisit interest at the Educational Dental Hospital of Jenderal Soedirman University. Method: The research used an observational analytical design with a cross-sectional approach. The sample taken for this study consists of 52 individuals using a total sampling technique. This research instrument uses a questionnaire on the marketing mix of dental mobile car, and a questionnaire on interest in repeat visits, distributed to respondents. Data were analyzed using Univariate and Bivariate analysis with Fisher’s Exact Test. Results: The results of this study indicate that there is a significant relationship between the marketing mix factors of product (p=0.016) and promotion (p=0.010). However, there is no significant relationship between the marketing mix factors of price (p=0.245), place (p=0.221), people (p=0.110), process (p=0.129), and physical evidence (p=0.481) with patient revisit interest at the Educational Dental Hospital of Jenderal Soedirman University. Conclusion: This research recommends that RSGMP Unsoed improve and optimize the factors of price, place, people, process, and physical evidence in order to increase the interest of patients to visit again.